A herança do esquecimento: saberes docentes nas narrativas de formação - Pedroso, Eliana Regina Fritzen (2015)
The present work fits the Research, Training, Knowledge and Professional Development (LP1) area, of the Postgraduate Program on Education of the Education Center, at the Federal University of Santa Maria (UFSM) and seeks explore the influences to the field of Education Philosophy on current teachers training in Brazil, approaching the research on this area and strengthening a process that is still recent, of thinking about the ethical and asthetical potential of the teaching knowledge. The need for this study is justified by the concern manifested in documents such as the National Curriculum Guidelines for the Undergraduate Course in Pedagogy (Brazil, 2006) and also by the theoretical and literature review, according to a critical-theoretical conception of education, in which the idea that the present time is substantially marked by the inheritance of forgetfulness underlies. The study was developed by means of a documental analysis of internship reports from the Pedagogy course of UFSM, following a qualitative approach and a hermeneutics-reconstructive understanding, outlining the present reports in the internship reports as training narratives. Therefore, the question is: how is the sensitivity in the training of teachers being developed for understanding of the remains of babarism in a time that is the heir of forgetfulness? Hence, the main objective of this research is to investigate the possibility of aggregating the asthetical-ethical horizon to the teaching knowledge, by means of the notion of experience, thematizing the narratives reverberated by the teachers under training in the time os forgetfulness. So, thinking about contributions about the pedagogical self-enlightenment of teaching provokes concern with the teaching rationality that circulates in the pedagogical environment. Within the work in question, this implies to assert how the practical-epistemological rationality, inserted in the syllabus of teachers training with some notion of knowledge and experience, limited to cognitiveness, contributed for the perpetuation of forgetfulness in the social sphere.